A Longitudinal Study of Predictors of Sexual Dysfunction in Men on Active Surveillance for Prostate Cancer. Issue 3 (30th July 2015) - Pearce, Shane M.; Wang, Chi‐Hsiung E.; Victorson, David E.; Helfand, Brian T.; Novakovic, Kristian R.; Brendler, Charles B.; Albaugh, Jeffrey A.
Abstract: Aim: The aim of this study was to examine the relationship between sexual dysfunction, repeat biopsies and other demographic and clinical factors in men on active surveillance (AS). Methods: Patient‐reported outcomes (PROs) measures were administered at enrollment and every 6 months to assess quality of life (QOL), psychosocial and urological health outcomes. Using mixed‐effects models, we examined the impact of repeat biopsies, total number of cores taken, anxiety, age, and comorbidity on sexual function over the first 24 months of enrolling in AS. Main Outcome Measures: PROs included the Expanded Prostate Cancer Index Composite‐26 (EPIC‐26) Sexual Function (SF) subscale, the American Urological Association‐Symptom Index (AUA‐SI), and the Memorial Anxiety Scale for Prostate Cancer (MAX‐PC). Results: At enrollment (n = 195), mean age was 66.5 ± 6.8 with a mean EPIC‐26 SF score of 61.4 ± 30.4. EPIC‐26 SF scores steadily decreased to 53.9 ± 30.7 at 24 months ( P < 0.01). MAX‐PC scores also progressively decreased over time ( P = 0.03). Factors associated with lower EPIC‐26 scores over time included age, unemployed status, diabetes, coronary artery disease, and hypertension (all P < 0.05). Higher prostate‐specific antigen (PSA) was associated with a more rapid decline in EPIC‐26 SF over time ( P = 0.03). In multivariable analysis, age, diabetes, and PSA × time interaction remained significant predictors of diminished sexual function. Anxiety, number of biopsies, and total cores taken did not predict sexual dysfunction or change over time in our cohort. Conclusions: Men on AS experienced a gradual decline in sexual function during the first 24 months of enrollment. Older age, PSA × time, and diabetes were all independent predictors of diminished sexual function over time. Anxiety, AUA‐SI, the number of cores and the number of biopsies were not predictors of reduced sexual function in men in AS.Pearce SM, Wang CHE, Victorson DE, Helfand BT, Novakovic KR, Brendler CB, and Albaugh JA. A longitudinal study of predictors of sexual dysfunction in men on active surveillance for prostate cancer. Sex Med 2015;3:156–164.